Off the track: A profile of non-tenure track faculty at McGill University - Speirs, Carol Cumming; Amsel, Rhonda; Baines, Malcolm G.; Pickel, Jo-Anne (Canadian Journal of Higher Education, 2017)
A survey conducted at McGill University suggests that non-tenure track faculty are a diverse group of highly-qualified individuals whose employment status involves a high degree of uncertainty. In accordance with other Canadian and American studies, the survey also found that a disproportionate number of women occupy non-tenure track as opposed to tenured or tenure track positions. Since the 1980s, North American universities have responded to increasing student enrollments and con- tinued cuts to government funding by appointing significant numbers of faculty to full-time and part-time non-tenure track positions. Due to the precariousness of their employment status, non-tenure track faculty rep- resent an attractive buffer in times of financial restraint. Despite their increasing numbers, however, little is known about the composition and concerns of non-tenure track faculty as a group. This article describes this group at one university and puts into question the structural and power relations that have led to their increased use and abuse.